Когда шагаешь по траве...: [о почвах : для сред. и ст. возраста] / В. Пальман - Пальман Вячеслав Иванович (Горизонты познания, 1991)
Экземпляры: КХ (20060330) / Инвентарный номер: 991202 / Сис.шифр: 40.3 / Авт.знак: П 14 / ГРНТИ: 68 / ББК: 40.3